(untitled) (African Human Mobility Review, 2021)
Violent attacks on African migrants have produced a richer body of knowledge on African transnational migration, xenophobia/Afrophobia, and their intersections with questions of citizenship and autochthony, especially in a country that historically has always been a home for African migrants. Constellations of narratives now vilify South Africa as a demonic state whose hatred of Africans and fixation on exorcising them have short-circuited the process of nation-building. The vilification of South Africa also tells us that many researchers, scholars, and even migrants are unaware of the ways that the country has transformed the lives of its increasing African migrant population. This article reflects on the changing material conditions of Cameroonians in South Africa to understand why this â€œAfrophobicâ€ state is still a key migration destination for Cameroonians. Drawing on personal exilic experiences, observations, and relevant literature, we argue that despite the victimization of Africans, including Cameroonians, this constitutional democracy has opened up political, economic and sociocultural opportunities for many Cameroonians residing permanently in the country. In forging this argument, the article interrogates the political landscape in Cameroon and examines key economic and sociocultural moments/activities in South Africa as well as accomplishments in this migrant community, to elicit how access to different opportunities in South Africa has significantly transformed the lives of Cameroonians.